Hydromineral recreational resources of Zhalanashkol lake (Journal of Geography and Environmental Management, 2018)
The article presents the results of research of physical and chemicalcomposition of water and medical mud of Zhalanashkollake. The scientificresearch and design studies for the study of the formation, supplyregime and medical mud of lakes in arid climate questions to assess thesuitability of hydromineral resources for the development of health tourismand recreation not been sufficiently developed. The absence in theliterature of a unified approach to the solution of precipitation processesin continental water bodies was the reason that since the summer 2012work began on the physico-chemical study of water and medical mud ofZhalanashkol lake.Physico-chemical study of water and medical mud isclosely linked with the problem of establishing necessity of determine theirsuitability for the development of health tourism and recreation. As a resultof expeditions and laboratory study established differences in the chemicalcompositionof water and medical mud western and eastern parts of thewater body. Hydromineral resources of Zhalanashkol lake are the productof a multi-purpose complex and can be used in the national economy andthe health the population.